Ensuring Legal Safeguards for Digitalized Social Services within the Framework of Government Decentralization - Ihor Panov; Kristina Petrosyan; Liudmyla Dobroboh; Valentyna Chernobuk; Yuliia Rashed (UIN Sunan Gunung Djati, 2023)
The purpose of the study is to digitize the social services system in the context of decentralization of power: legal regulation and areas of improvement. Main content. It has been established that new online services are being introduced in Ukraine to enable consumers to receive such services virtually. In our opinion, in the future, these services should simplify the procedure for access to them, taking into account the entities which are primarily interested in using them, and expand the scope of their provision: from informing the consumer to obtaining the result. The society and science development requires the introduction of new technologies into the service system. It has been concluded that the need to use information technologies in judicial proceedings is due to the global informational support of modern society, and development of new interaction forms in the social area using electronic means of communication: the global Internet, mobile and satellite communication systems. The author reveals the essence of